Cover Image, Volume 53, Issue 2. (27th February 2020) - Rong, Qiong; Li, Shuyi; Zhou, Yang; Geng, Yuanming; Liu, Shangbin; Wu, Wanqiu; Forouzanfar, Tim; Wu, Gang; Zhang, Zhiyong; Zhou, Miao
Abstract : The cover image is based on the Original Article A novel method to improve the osteogenesis capacity of hUCMSCs with dual‐directional pre‐induction under screened co‐culture conditions by Qiong Rong et al., https://doi.org/10.1111/cpr.12740 .